Social Minds and Metaphor in Rousseau - Sinding, Michael (Narrative, 2015)
Rousseau’s writings seem to call out for analysis in terms of social minds, because he looms so large in the conceptual framing of modern psychosocial dynamics in their primary units, and the narrative framing of them in their primary cultural genres. He did much to invent our ideas of the solitary individual in autobiography, friends and lovers in the sentimental novel, and democratic societies in political philosophy. If narratology needs to address the “formation, development, maintenance, modification, and breakdown of . . . intermental systems” (Palmer 41), and metaphor is among our central instruments for conceptualizing and expressing such subjective and abstract matters, then narratology should get metaphorical. Underlying Rousseau’s revolutionary writings on social minds are multiple models of intermentality, built partly from particular combinations of metaphors. To understand how intermentality is narrated, we need to understand how metaphors are narrated. I develop this perspective by comparing the role of metaphor in framing kinds of social minds in Rousseau's novel Julie (1761) and his treatise The Social Contract (1762).
Keywords: social minds; metaphor; fictional narrative; factual narrative; Rousseau